ANALISIS TEKNIKAL HARGA SAHAM PT. ADIRA DINAMIKA MULTI FINANCE Tbk. DI MASA COVID 19 DENGAN METODE ARIMA - Khotmi, Herawati; Wardiningsih, Reny (Universitas Islam Negeri Mataram, 2020)
This study aims to analyze and predict stock prices using technical analysis at PT. Adira Dinamika Multi Finance, Tbk by ARIMA method. Data collection technique used is archival data collection which comes from secondary data. Secondary data in this study’s from daily data on ADMF shares in 2nd January 2020-26th October 2020 which is sourced from finance.yahoo.com. The analysis technique used in this research is the Box-Jenkins method with three stages, i.e. the first stage of identification and specification of ARIMA model (p, d, q), the second stage is prediction stage, the third stage is diagnosis model. This study results show that the MA Model (2) is the best model whose data describes ADMF stock price movements during the pandemic period and produces a difference between the real data and forecast is not too different. Where on average there’s a difference about Rp. 43.5 between the real stock price data with forecast data. Suggestions for future researchers to use fundamental analysis to support investment decisions.